APLIKASI PEMELIHARAANPREVENTIVE MESIN PRODUKSI DENGAN METODE “SMART MAINTENANCE” UNTUK EFISIENSI PERUSAHAAN LUCKY OLYMPIC KEDIRI - Eko Siswanto (Universitas Islam Kadiri, 2019)
Availability and reliability are still less can degrade performance (performance) of a machine, which can lead to production targets are not met. Implementation of the repair machinery for this is not trustworthy, the maintenance management system